Gut microbiota dysbiosis and diarrhea in kidney transplant recipients. Issue 2 (21st July 2018) - Lee, John Richard; Magruder, Matthew; Zhang, Lisa; Westblade, Lars F.; Satlin, Michael J.; Robertson, Amy; Edusei, Emmanuel; Crawford, Carl; Ling, Lilan; Taur, Ying; Schluter, Jonas; Lubetzky, Michelle; et al.
Abstract : Posttransplant diarrhea is associated with kidney allograft failure and death, but its etiology remains unknown in the majority of cases. Because altered gut microbial ecology is a potential basis for diarrhea, we investigated whether posttransplant diarrhea is associated with gut dysbiosis. We enrolled 71 kidney allograft recipients for serial fecal specimen collections in the first 3 months of transplantation and profiled the gut microbiota using 16S ribosomal RNA (rRNA) gene V4‐V5 deep sequencing. The Shannon diversity index was significantly lower in 28 diarrheal fecal specimens from 25 recipients with posttransplant diarrhea than in 112 fecal specimens from 46 recipients without posttransplant diarrhea. We found a lower relative abundance of 13 commensal genera (Benjamini‐Hochberg adjusted P ≤ .15) in the diarrheal fecal specimens including the same 4 genera identified in our prior study. The 28 diarrheal fecal specimens were also evaluated by a multiplexed polymerase chain reaction (PCR) assay for 22 bacterial, viral, and protozoan gastrointestinal pathogens, and 26 specimens were negative for infectious etiologies. Using PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) to predict metagenomic functions, we found that diarrheal fecal specimens had a lower abundance of metabolic genes. Our findings suggest that posttransplant diarrhea is not associated with common infectious diarrheal pathogens but with a gut dysbiosis. Abstract : This study utilizes 16S rRNA gene deep sequencing to profile gut microbiota in kidney transplant recipients with and without diarrhea and reports that most posttransplant diarrhea early after transplantation is not associated with infectious etiologies but with gut microbiota dysbiosis.